Pengaruh media AR Book terhadap peningkatan pengetahuan dan sikap gizi seimbang pada anak usia sekolah - Putri, Vira Herliana; Sitoayu, Laras; Ronitawati, Putri (Jurusan Gizi Politeknik Kesehatan Kemenkes Aceh, 2021)
Stunting in school-age children is still a problem in Indonesia, including chronic malnutrition. One of the causes is the lack of good knowledge about balanced nutrition. Increasing knowledge of balanced nutrition in school-age children can use AR Books, and students are exposed to real objects that are studied. This study aims to determine the provision of AR Book media to increase knowledge and attitudes of balanced nutrition for school-age children. The research design used Quasy Experimental through a pre-post test control group design. The sample size is 65 students, 27 students in the intervention group and 38 students in the control group. Measurements of pre-test and post-test were carried out in each group, with a duration of up to two weeks. Data analysis used Paired Sample T-Test, Wilcoxon, Independent T-test, and Mann Whitney. The results showed an increase in the average score of nutritional knowledge in the intervention group using AR Book by 77,8, and attitudes about nutrition also increased by 92,0. The provision of AR Book media affects increasing knowledge of balanced nutrition (p= 0,0001) and balanced nutrition attitudes (p= 0,001). In conclusion, the AR Book media on balanced nutrition is one of the alternative educational media that can be used to increase knowledge and attitudes of balanced nutrition in elementary school-aged children